Polymerization-induced self-assembly of block copolymer nanoparticles via RAFT non-aqueous dispersion polymerization. (January 2016) - Derry, Matthew J.; Fielding, Lee A.; Armes, Steven P.
Abstract: There is considerable current interest in polymerization-induced self-assembly (PISA) via reversible addition–fragmentation chain transfer (RAFT) polymerization as a versatile and efficient route to various types of block copolymer nano-objects. Many successful PISA syntheses have been conducted in water using either RAFT aqueous dispersion polymerization or RAFT aqueous emulsion polymerization. In contrast, this review article is focused on the growing number of RAFT PISA formulations developed for non-aqueous media. A wide range of monomers have been utilized for both the stabilizer and core-forming blocks to produce diblock copolymer nanoparticles in either polar or non-polar media (including supercritical CO2 and ionic liquids) via RAFT dispersion polymerization. Such nanoparticles possess spherical, worm-like or vesicular morphologies, often with controllable size and functionality. Detailed characterization of such sterically stabilized diblock copolymer dispersions provides important insights into the various morphological transformations that can occur both during the PISA synthesis and also on subsequent exposure to a suitable external stimulus (e.g. temperature).